The Application of Brain Organoid Technology in Stroke Research: Challenges and Prospects - Song, Guini; Zhao, Min; Chen, Hanmin; Zhou, Xiangyue; Lenahan, Cameron; Ou, Yibo; He, Yue (Frontiers in Cellular Neuroscience, 2021)
Stroke is a neurological disease responsible for significant morbidity and disability worldwide. However, there remains a dearth of effective therapies. The failure of many clinical trials in stroke has promoted the development of human cell-based models, such as brain organoids. Brain organoids differ from pluripotent stem cells in that the former have recapitulated various key features of the human central nervous system (CNS) in three-dimension (3D) space. Recent studies have demonstrated that brain organoids could serve as a new platform to study various neurological diseases. However, there are several limitations, such as scarcity of glia and vasculature, which are important in studying stroke. Herein, we have summarized the application of brain organoid technology in stroke, such as in modeling and transplantation. We also discuss methods to overcome the limitations, as well as future prospects for its application in stroke research. Although there are many difficulties and challenges in brain organoids technology, it is definite that this technology will play a critical role in the exploration of future stroke treatment.